An online information security Aaareness model: the disclosure of personal data - Parker, Heather Joubert (Rhodes University, Faculty of Commerce, Department of Information Systems, 2021)
Social media has revolutionized the way people send and receive information by creating a new level of interconnected communication. However, the use of the Internet and social media brings about various ways in which a user's personal data can be put at risk. This study aims to investigate what drives the disclosure of personal information online and whether an increase in awareness of the value of personal information motivates users to safeguard their information. Fourteen university students participated in a mixed-methods experiment, where they completed a questionnaire before and after being shown the data stored about them by online platforms to determine if changes occur in their intention to disclose. Following completing the initial questionnaire, the participant viewed the personal data stored about them by Facebook, Google, and Instagram. Other online tools such as Social Profile Checker, Facebook View As, and HaveIBeenPawned were used to see the information publicly available about each participant. Together these findings were discussed in a semi-structured interview to determine the influence of attitudes, subjective norms, and awareness on the cost-benefit analysis users conduct when disclosing information online. Overall, the findings indicate that users are able to disregard their concerns due to a resigned and apathetic attitude towards privacy. Furthermore, subjective norms enhanced by FOMO further allow users to overlook potential risks to their information in order to avoid social isolation and sanction. Alternatively, an increased awareness of the personal value of information and having experienced a previous privacy violation encourage the protection of information and limited disclosure. Thus, this study provides insight into privacy and information disclosure on social media in South Africa. It reveals more insight into the cost-benefit analysis users conduct by combining the Theory of Planned Behaviour with the Privacy Calculus Model, as well as the antecedent factors of Trust in the Social Media Provider, FOMO, and Personal Valuation of Information.
Keywords: Social media -- Psychological aspects; Social media -- Psychological aspects -- South Africa; Human behavior; Disclosure of information -- Psychological aspects -- Case studies; Personal information management -- Psychological aspects -- Case studies; Data protection -- Psychologial aspects -- Case studies